The Effect Of Variations Of Zig-Zag Running Training On The Ability Of Drilling In Football Extracurricular in SMP Raudlatul Ulum - Mohammad Rizal; Khoirul Anwar; Septyaningrum Putri Purwoto; Fajar Hidayatulloh (UNIVERSITAS NEGERI MAKASSAR, 2022)
Physical Education is a physical activity organized to be a medium for educational activities. Extracurricular activities are learning activities outside of extracurricular activities. Football is one of the most popular sports in the world, including in Indonesia. The type of research used in this research is the experimental method. The method used in this study is the zigzag running method. The population and sample in this study amounted to 20 people. Based on the results of the research, the normality test is 0.172, which means > 0.05 with a normal distribution, the homogeneity test results get a value of 0.079 and 1,000, which means <0.05 is declared homogeneous, while the t-test results show that the significant value is 0.000, meaning less than 0.05, then Ho is rejected. This shows that there is a significant difference between before and after giving the zigzag running training method to students.